Quality, excellence and culture in the pursuit of organizational agility - Carvalho, André Mendes (2017)
Operational excellence programs have proved to be valuable in helping companies improve their quality practices and their performance. However, after some time, these programs seem to stagnate and to be unable to keep pushing organizations forward. We believe that this problem is due to the lack of integration between excellence and agility, which we see as a natural goal for organizations that wish to promote a true culture of excellence in face of highly unstable business environments. This paper presents our research approach to the problem, and early results from investigating the influence of a culture of excellence in promoting an enduring capacity to change.